EXERCISE TRAINING IMPROVES ENDOTHELIAL FUNCTION IN RESISTANCE ARTERIES OF YOUNG PREHYPERTENSIVES - Beck, Darren T. (2013)
Prehypertension is associated with reduced conduit artery endothelial function and perturbation of oxidant/antioxidant status. It is unknown if endothelial dysfunction persists to resistance arteries and if exercise training effects oxidant/antioxidant balance in young prehypertensives. We examined resistance artery function using venous occlusion plethysmography measurement of forearm (FBF) and calf blood flow (CBF) at rest and during reactive hyperemia, as well as lipid peroxidation (8-iso-PGF(2α)) and antioxidant capacity (Trolox-equivalent antioxidant capacity; TEAC) before and after exercise intervention or time-control. Forty-three unmedicated prehypertensive and fifteen matched normotensive time-controls met screening requirements and participated in the study (age: 21.1±0.8 years). Prehypertensive subjects were randomly assigned to resistance exercise training (PHRT; n=15), endurance exercise training (PHET; n=13) or time-control groups (PHTC; n=15). Treatment groups exercised 3 days per week for 8 weeks. Peak and total FBF were lower in prehypertensives than normotensives (12.7±1.2 ml/min/100ml tissue and 89.1±7.7 ml/min/100ml tissue vs. 16.3±1.0 ml/min/100ml tissue and 123.3±6.4 ml/min/100ml tissue, respectively; p<0.05). Peak and total CBF were lower in prehypertensives than normotensives (15.3±1.2 ml/min/100ml tissue and 74±8.3 ml/min/100ml tissue vs. 20.9±1.4 ml/min/100ml tissue and 107±9.2 ml/min/100ml tissue, respectively; p<0.05). PHRT and PHET improved humoral measures of Trolox-equivalent antioxidant-capacity (TEAC) (+24% and +30%) and 8-iso-PGF(2α) (−43% and −40%, respectively; p<0.05). This study provides evidence that young prehypertensives exhibit reduced resistance artery endothelial function and that short term (8weeks) resistance or endurance training are effective in improving resistance artery endothelial function and oxidant/antioxidant balance in young prehypertensives.